Social networking in charity advocacy - Wong, Diana M. L.; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Online charity website at present is not gaining continuous support from the community which resulted in the stagnant progress for charity work in Malaysia. The paper explores the motivation behind charity related issues and studies the influence of web integration of social networking tools in promoting charity work. The study proposes a solution of developing GiFT-a one stop charity portal with integrated social networking tools. The portal provides a gateway to connect people to charity organizations in support of charity movement in Malaysia. The motivation factor stems from the social networking tools in cultivating the sense of belonging to a community of shared interest. It is hope that the subsequent study will not limit to groups of individual users but can also be proliferated into corporate effort for corporate social responsibility.